Child health outcomes following fertility treatment and patient characteristics: discrepancies, limitations and prudence. (1st December 2020) - Wilkinson, Jack; Navarro-Rubio Coello de Portugal, Sonsoles; Huang, Jonathan; Güell, Francisco
Abstract: We argue that increased risk for a variety of diseases in ART children has been consistently reaffirmed by different methods and in diverse populations, providing a methodological critique of recent sibling studies, which hold great potential for studying the risks of ART. A recent within-family analysis using a national population register holds a distinct size advantage over previous studies, and suggested that apparent risks to offspring may be attributable to birth order. However, limitations of the design may have resulted in an erroneous conclusion. We discuss the advantages of a frequently neglected sibling study design, which compares siblings born of surrogate motherhood. While uncertainty remains, the evidence points to elevated risk for ART offspring. It may therefore be prudent to call for an extension of preventive and precautionary decisions to the entire population, and to change informed consent to incorporate the long-term health consequences of fertility treatments.